Utilization of hydrosilated silica-based stationary phases for separation of antioxidants - Soukup, Jan; Janás, Petr; Jandera, Pavel (Univerzita Pardubice, 2014)
We studied the influence of mobile phase composition on the retention of phenolic acids and flavonoid compounds on five different hydrosilated silica-based stationary phases in buffered aqueous acetonitrile. Cogent UDC cholesterolTM, Cogent bidentate C18TM and Cogent Phenyl hydrideTM columns show significant dual reversed-phase/normal-phase retention behavior, while Cogent Diamond hydrideTM and Cogent Silica-CTM columns provide very low retention in the reversed-phase mode. The effect of the aqueous acetate buffer concentration on retention factors of phenolic acids and flavonoid compounds over the full mobile phase composition range, including both aqueous normal-phase (ANP) and reversed-phase (RP) mechanisms, can be described by a four-parameter equation for dual-retention mechanism. At increasing temperature, the retention factors and peak widths decrease in the aqueous normal-phase range. In agreement with van’t Hoff model, linear ln k versus 1/T plots were observed, showing a single retention mechanism. From among the stationary phases tested, Cogent UDC cholesterolTM column has high temperature stability (up to 100/C) and provides most selective and efficient separations of flavones in the ANP mode and Cogent Diamond hydrideTM is the most selective and effective for separation of phenolic acids.
Využití hydrosilovaných stacionárních fází pro separaci antioxidantů
Keywords: hydrosilated silica; HILIC; antioxidants; hydrosilovaný silikagel; antioxidanty